التنويع الاقتصادي كآلية للدفع نحو الإقلاع الاقتصادي - شيخة مبروك ،العروسي (جامعة الوادي University of Eloued, 2025)
تهدف الدراسة الحالية إلى محاولة كشف وتقييم مدى نجاح وصول دولة الإمارات إلى الإقلاع الاقتصادي، من خلال تبني استراتيجيات التنويع الاقتصادي على اعتباره خيارا استراتيجيا، بالإضافة إلى الوقوف على بعض المؤشرات الكلية للاقتصاد الإماراتي وتحديد دورها في عملية الإقلاع الاقتصادي، ولتحقيق أهداف الدراسة اُعتمد في الجانب النظري على المعلومات المستقاة من الدراسات السابقة العربية منها والأجنبية، أما الجانب التطبيقي فقد اعتمدت على مؤشر هرفندل هيرشمان لحساب التنويع الاقتصادي لبعض المؤشرات الكلية للاقتصاد خلال فترة الدراسة. حيث توصلت الدراسة إلى نجاح منظومة التنويع الاقتصادي الإماراتي، في ظل ما تتمتع به من بنية تحتية متطورة، إلى جانب مرونة القوانين والتشريعات، بالإضافة إلى جاذبية مناخ الاستثمار. The current study aims to attempt to reveal and evaluate the extent of the UAE's success in achieving economic take-off, by adopting economic diversification strategies as a strategic option, in addition to identifying some of the overall indicators of the UAE economy and determining their role in the economic take-off process. To achieve the objectives of the study, the theoretical aspect was based on information obtained from previous studies, both Arab and foreign, while the applied aspect was based on the Herfindahl Hirschman index to calculate the economic diversification of some of the overall indicators of the economy during the study period. The study concluded that the UAE's economic diversification system has been successful, given its advanced infrastructure, flexible laws and legislation, and attractive investment climate.
Economic diversification as a mechanism for economic take-off - A study of the UAE during the period (2010-2023)-
Keywords: تنويع اقتصادي; إقلاع اقتصادي; دولة الإمارات; Economic diversification; Economic takeoff; UAE.